Case Report: Anti-N-Methyl-D-Aspartate Receptor Encephalitis Manifesting With an Isolated Psychiatric Episode and Normal Ancillary Tests - Pavǎl, Denis; Cîmpan, Claudia Mihaela; Gherghel, Nicoleta; Damian, Laura Otilia; Tohǎnean, Nicoleta; Micluţia, Ioana Valentina (Frontiers in Psychiatry, 2022)
The majority of patients with anti-N-Methyl-D-Aspartate receptor (NMDAR) encephalitis present with psychiatric symptoms and subsequently develop neurological features. However, isolated psychiatric episodes occur in <5% of affected individuals, less frequent at disease onset (<1%) compared to relapse (4%). We report the case of a previously healthy 24-year-old female who presented with psychotic symptoms and behavioral alterations. Despite therapy, she showed no improvement and subsequently developed catatonic features. While the ancillary tests were normal, the clinical warning signs raised the suspicion of anti-NMDAR encephalitis which we later confirmed. Given its strong association with underlying tumors, we screened the patient and found an ovarian teratoma. Once removed, the patient displayed a substantial improvement in the mental status. Besides being extremely rare, this case illustrates the need to maintain clinical suspicion of anti-NMDAR encephalitis even in the absence of neurological features or paraclinical anomalies.